Comparative STAT3-Regulated Gene Expression Profile in Renal Cell Carcinoma Subtypes - Robinson, Rebekah L.; Sharma, Ashok; Bai, Shan; Heneidi, Saleh; Lee, Tae Jin; Kodeboyina, Sai Karthik; Patel, Nikhil; Sharma, Shruti (Frontiers in Oncology, 2019)
Renal cell carcinomas (RCC) are heterogeneous and can be further classified into three major subtypes including clear cell, papillary and chromophobe. Signal transducer and activator of transcription 3 (STAT3) is commonly hyperactive in many cancers and is associated with cancer cell proliferation, invasion, migration, and angiogenesis. In renal cell carcinoma, increased STAT3 activation is associated with increased metastasis and worse survival outcomes, but clinical trials targeting the STAT3 signaling pathway have shown varying levels of success in different RCC subtypes. Using RNA-seq data from The Cancer Genome Atlas (TCGA), we compared expression of 32 STAT3 regulated genes in 3 RCC subtypes. Our results indicate that STAT3 activation plays the most significant role in clear cell RCC relative to the other subtypes, as half of the evaluated genes were upregulated in this subtype. MMP9, BIRC5 and BCL2 were upregulated and FOS was downregulated in all three subtypes. Several genes including VEGFA, VIM, MYC, IGB4, ICAM1, MMP1, CCND1, STMN1, TWIST1 and PIM2 had variable expression in RCC subtypes and are potential therapeutic targets for personalized medicine.